Application of Balaghah Learning at Mahad Darussalam Kersamanah Garut - Busyro, Ahmad (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
Balaghah as one of the branches of Arabic language that studies beauty and fluency. Islamic boarding schools play an important role in the development of teaching science as a complement to the science of tools, however, in its implementation it still faces significant challenges. This research uses a qualitative research approach. The method used is field research. Data collection techniques through observation, interviews and documentation. Step-by-step data analysis; identification, classification, interpretation, drawing conclusions, then data validation tests. The results of the study show that the implementation of Balaghah learning at the Darussalam Kersamanah Islamic Boarding School is based on various religious, cultural, linguistic, and literary factors. The curriculum implemented is a combination of the modern pesantren system and traditional salaf. Teaching is carried out with an integrative approach, which combines theory and practice in a balanced manner, Balaghah teachers in this hut use various teaching methods and strategies such as direct, inductive methods and dialogical discussions supported by mature teacher preparation both individually and administratively. The existence of experts, competent teachers, and reliable references are factors for learning effectiveness. In addition, it was found that the support of a conducive learning environment and the variety of linguistic activities of students greatly contributed to the effectiveness of Balaghah learning. This study concludes that the success of the implementation of Balaghah learning at the Darussalam Kersamanah Islamic Boarding School is greatly influenced by the role of experts, the combination of teaching methods used, the quality of teachers and their good interaction with students, the support of the learning environment and the variety of Arabic language activity programs.